Historical Society of the District of Columbia Circuit. Oral History Project oral history interviews - Historical Society of the District of Columbia Circuit. Oral History Project
Transcripts of oral history interviews documenting the history of the circuit, containing biographical information and discussions of the judicial process, history of the circuit, evolution of significant cases, and the role of law clerks. Includes interviews with judges, judges' spouses, lawyers, and court staff associated with the U.S. Circuit Court for the District of Columbia. Interviewees include Robert S. Bennett, Robert H. Bork, James Lane Buckley, Lloyd N. Cutler, Samuel Dash, Gerhard Alden Gesell, David Ginsburg, Erwin N. Griswold, Harold H. Greene, Abner J. Mikva, E. Barrett Prettyman, Joseph L. Rauh, Patricia M. Wald, Paul C. Warnke, and Helen Patton Wright. Each transcript is supplemented by an index.
The Oral History Project of the Historical Society of the District of Columbia Circuit was created in 1991 to preserve the recollections of the judges who sat on the U.S. courts of the District of Columbia Circuit, and judges' spouses, lawyers, and court staff.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bennett, Robert S. -- Interviews; Bork, Robert H. -- Interviews; Buckley, James Lane, -- 1923- -- Interviews; Cutler, Lloyd N. -- Interviews; Dash, Samuel -- Interviews; Gesell, Gerhard Alden, -- 1910-1993 -- Interviews; Ginsburg, David, -- 1912-2010 -- Interviews; Griswold, Erwin N. -- 1904-1994 -- Interviews; Greene, Harold H. -- Interviews; Mikva, Abner J. -- Interviews; Prettyman, E. Barrett -- 1925- -- Interviews; Rauh, Joseph L., -- 1911- -- Interviews; Wald, Patricia M. -- Interviews; Warnke, Paul C., -- 1920- -- Interviews; Wright, Helen Patton, -- 1919- -- Interviews; United States. -- Circuit Court (District of Columbia); Circuit courts -- Washington (D.C.); Judges -- Interviews; Judges' spouses -- Interviews; Judicial process; Law clerks; Lawyers -- Interviews